Pengembangan Komunikasi Berbahasa Inggris Dalam Upaya Meningkatkan Potensi Pariwisata Desa Mekarbuana Tegalwaru Kabupaten Karawang - Meiyanti Nurchaerani; Alfian (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Tourism development, especially in Mekarbuana Tegalwaru Village in Karawang Regency. This must be supported by the English language skills of the villagers who should be ready to receive foreign tourists who come. But in reality their abilities tend to be relatively low because on average they have a minimal educational background. Based on this statement, our community service team focused on community service to improve daily activity conversation in English. The community service training program resulted in an increase in the ability to speak and communicate in English, increased management that supports the promotion of the village, increased bias to communicate properly and correctly. During the tourism activities in Mekarbuana Village, Karawang Regency, the government and the community have worked together to improve tourism in their area.